Faith, Morality, and Civil Society - Lawler, Peter Augustine; McConkey, Dale (Lexington Books, 2003)
In this rich collection of essays, editors Dale McConkey and Peter Augustine Lawler explore the contributions that religious faith and morality can make to a civil society. Though the level of religious expression has remained high in the United States, the shift from traditional religious beliefs to a far more individualized style of faith has led many to contend that no faith commitment, collective or personal, should contribute to the vibrancy of a civil democratic society. Challenging those who believe that the private realm is the only appropriate locus of religious belief, the contributors to this volume believe that religion can inform and invigorate the secular institutions of society such as education, economics, and politics. Drawn from a wide variety of religious and moral traditions, these diverse essays show, from many perspectives, the important contribution religion has to make in the public square that is civil society.